Prediction value of heart rate combined with arteriosclerosis index for left coronary artery lesion in patients with ACS - Bike Bie; Dezhong Yang (BMC Cardiovascular Disorders)
Abstract Objective This study aims to evaluate the predictive value of heart rate combined with arteriosclerosis index on the degree of left coronary artery(LCA) lesions in patients with acute coronary syndromes(ACS). Methods Patients diagnosed with ACS who were discharged from the Department of Cardiovascular Medicine of the Army Characteristic Medical Center from 2019 to 2024 were included, and the relevant clinical data of the selected patients were collected through the electronic medical record database system. According to the results of coronary angiography, they were divided into mild lesion group (All lesions in the left coronary artery (including its branches) with a stenosis degree less than 70%, n = 121) and severe lesion group (any one or more vessels (including their branches) in the left coronary artery with a stenosis degree of 70% or more was the severe lesion group, n = 264). Results In ACS patients with concomitant LCA and right coronary artery (RCA) lesions, the results of Spearman correlation analysis indicated that heart rate (r = 0.1948, P = 0.0001) and arteriosclerosis index (r = 0.1636, P = 0.0013) were positively correlated with the Gensini score of the LCA in coronary angiography. The results of multivariate logistic regression analysis suggested that heart rate (HR:1.062, 95%CI:1.040–1.083, P < 0.001), arteriosclerosis index (HR:1333, 95%CI:1.045–1.699, P = 0.021), and age (HR:1.023, 95%CI:1.003–1.042, P = 0.021) were all independent predictors of severe lesions in the LCA. The ROC curve showed that heart rate(AUC = 0.70) and arteriosclerosis index(AUC = 0.59) had certain predictive value for the degree of LCA lesions, and the predictive value of combined assessment was higher (AUC = 0.72). In ACS patients with isolated LCA lesions, both HR (r = 0.0299, P = 0.7424) and AI (r = 0.1930, P = 0.0325) remained positively correlated with the severity of LCA lesions. The results of multivariate logistic regression analysis suggested that heart rate (HR:1.044, 95%CI:1.004–1.085, P = 0.032) and arteriosclerosis index (HR:1.72, 95%CI:1.001–2.955, P = 0.049) were all independent predictors of severe lesions in the LCA. The ROC curve showed that heart rate(AUC = 0.64) and arteriosclerosis index(AUC = 0.64) had certain predictive value for the degree of LCA lesions, and the predictive value of combined assessment was higher (AUC = 0.71). Conclusions The combination of HR and AI demonstrates predictive value for LCA lesion severity in ACS patients.